Vaginal Cuff Dehiscence Presenting with Free Air 60 Days after Robotic-Assisted Hysterectomy - D. Munger; M. Iannamorelli; C. Galvez; C. Service (Case Reports in Surgery)
Introduction. The vast majority of patients presenting with pneumoperitoneum have visceral organ perforation and require urgent diagnostic laparoscopy. Nonsurgical causes are relatively rare and may be attributed to multiple etiologies. Case Presentation. Here we describe the case of a 38-year-old Caucasian female who presented to the emergency department with three days of cramping, epigastric abdominal pain. Her physical exam was notable for tenderness to palpation in the epigastric area and abdominal and chest X-rays showed free air under the diaphragm. Free air around the porta hepatis was verified on CT scan. Approximately 90% of pneumoperitoneum cases are due to perforation of visceral organs and therefore require operative management. An urgent exploratory laparoscopy revealed no clear source of free air, but postoperatively the patient developed a large volume of watery discharge from her vagina. Subsequent workup revealed a 1 cm vaginal cuff dehiscence which was later repaired with no postoperative complications. Conclusion. Although the majority of patients with pneumoperitoneum require urgent exploratory laparoscopy, a careful diagnostic workup may reveal sources of free air that are not related to hollow viscous perforation. Vaginal cuff dehiscence represents a rare yet nonurgent source of pneumoperitoneum. This differential should be considered in light of the possible intra- and postoperative complications of surgery.